DIGESTIBLE ENERGY OF UNPEELED CASSAVA ROOT MEAL AND ITS EFFECT ON GROWTH PERFORMANCE AND CARCASS TRAITS IN RABBITS - Mora, L. M.; Moura, Ana Silvia Alves Meira Tavares [UNESP]; Scapinello, C.; Bicudo, S. J. [UNESP]; Araujo, I. G.; Curcelli, F. [UNESP]; Barros, T. F. M. [UNESP] (Univ Politecnica Valencia, 2014)
Two experiments were conducted to evaluate the use of cassava root meal (891 g dry matter [DM]/kg, 639 g starch/kg, 74.1 g neutral detergent fibre [NDF]/kg, and 26.6 g crude protein [CP]/kg) in diets for growing rabbits. In the first experiment, a basal diet (419 g NDF/kg and 181 g CF/kg) and a test diet, in which cassava replaced 25% of the DM of the reference diet, were used. Twenty 50-d-old New Zealand White rabbits weighing 1474 +/- 10 g were randomly assigned to the 2 treatments, and digestibility of DM and gross energy (GE) were determined. The inclusion of cassava root meal in the diet increased DM digestibility (67.0 +/- 0.80 vs. 58.0 +/- 1.12%, P<0.01) and digestible energy (DE) content (11.86 +/- 0.16 vs. 10.45 +/- 0.22 MJ/kg, P<0.01). Digestible DM and DE contents of the unpeeled cassava root meal, obtained by the substitution method, were 943.3 +/- 15.8 g/kg and 15.28 +/- 0.32 MJ/kg. In the second experiment, 5 experimental diets were formulated to contain 150 g CF/kg, 184 g acid detergent fibre/kg and 10.9 MJ DE/kg, and increasing levels (0, 7, 14, 21 and 28%) of unpeeled cassava root meal, mainly in substitution of corn. A growth trial was carried out using 90 rabbits from the Botucatu genetic group from weaning (35 d, weighing 951 13 g) up to 71 d of age. The rabbits were housed in pairs, and randomly assigned to the 5 treatments (9 replicates/ treatment). No effect of the substitution of corn with cassava root meal was detected on growth performance (growth rate, feed intake and feed conversion ratio, on ay. 44.6 +/- 0.50 g/d, 132 +/- 1.4 g/d and 2.97 +/- 0.028 g/g, respectively). The level of inclusion of cassava root meal had a quadratic effect (P=0.005) on the dressing out percentage, showing a minimal value (51.2%) for inclusion of 139 g/kg. No other effect was observed on slaughter and reference carcass weights (2383 19 and 1238 11 g, respectively). Unpeeled cassava root meal may be used to completely replace corn in the diet, supporting high performance in growing rabbits, but its effects on carcass traits should be investigated further.
Keywords: digestibility; growth performance; Manihot esculenta